Application of workload indicators to assess the allocation of orthopedists in a national referral hospital in Brazil - Claudia Regina Machado; Deise Brasil; Mario Roberto Dal Poz (BMC, 2022)
Abstract Background The study analyzes the allocation of specialized doctors' orthopedists in a high-complex hospital, using the WHO's Workload Indicators of Staffing Need (WISN) methodology and approach, which measures the workload pressure on the healthcare team (positive, negative, or well-adjusted). Methods In the first phase, the hospital's operations and activities were analyzed using the information system. The duration of the tasks performed by the specialist physicians was observed and directly measured in the second phase. Finally, the indicators were analyzed, and the workload was calculated using the WISN application. The measurement was made using the available work time per year divided by the time unit over the previous 12 months. Results The hand surgery care unit was WISN 1.0 and the ratios for the spine surgery care unit was 1.22, indicating enough physicians and no work overload among the groups surveyed. The ratio in the knee unit was 1.69, indicating that there was an excess of staffing for the workload. Conclusion The workload findings and staffing calculations were useful in supporting and orienting the design and implementation of measures to increase the efficiency and effectiveness of health services.